2017
DOI: 10.1016/j.micres.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Azospirillum spp.: Limitations of 16S rRNA and qualities of rpo D as genetic markers

Abstract: Since their discovery, plant-growth promoting rhizobacteria from the genus Azospirillum have been subjected to intensive research due to their biotechnological potential as crop inoculants. Phylogenetic analysis of Azospirillum spp. is carried out by 16S rRNA sequencing almost exclusively, but inconsistencies and low confidence often arise when working with close species. In this work, it was observed that these difficulties might be explained by a high number of rRNA operons with considerable inter-genic vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 41 publications
1
18
0
1
Order By: Relevance
“…Notably, previous results on whole genome comparisons indicated that Az39, which has been historically considered as an A. brasilense strain, might be part of a different species (Maroniche et al, 2017). Thus, taken together, all the evidences suggest that Az39, as well as strains Az3, Az19 and Az63, do not belong to A. brasilense species.…”
Section: Genotyping and Characterization Of Azospirillum Strainsmentioning
confidence: 81%
See 3 more Smart Citations
“…Notably, previous results on whole genome comparisons indicated that Az39, which has been historically considered as an A. brasilense strain, might be part of a different species (Maroniche et al, 2017). Thus, taken together, all the evidences suggest that Az39, as well as strains Az3, Az19 and Az63, do not belong to A. brasilense species.…”
Section: Genotyping and Characterization Of Azospirillum Strainsmentioning
confidence: 81%
“…Further studies will be needed to determine the behavior of this strain in field trials in view of developing new inoculants suitable for areas with water deficit. Table 2 or elsewhere (Maroniche et al 2017). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the complexity of the microbiome associated with plants, the analyses of the purine metabolism will concentrate mainly on bacteria, with emphasis on the bacterial species or isolates fully identified with 98-100% similarity with reference strains. The names of the bacterial species are mentioned as in the cited references, although we are aware of the recent re-classification of a number of Pseudomonas and Azospirillum strains into different genospecies (Tran et al 2017;Maroniche et al 2017) as well as of the split of the genera Burkholderia and Paraburkholderia (Martínez-Hidalgo and Hirsch 2017).…”
mentioning
confidence: 99%